Studying the Level of Teachers' Use of Innovative Methods (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study analyzes the level of teachers' use of innovative pedagogical methods. The objective is to identify the role of teachers and their methodological approaches in selecting educational technologies to develop foundational competencies in students. The research argues that a subject teacher must determine the core competencies defined for the class and topic in their lesson plan, carefully choosing teaching methods and approaches accordingly. It emphasizes the necessity to pre design pedagogical technologies and guarantee positive outcomes, measured by how well students master the learning material. Furthermore, the study highlights that enhancing teachers' qualifications and equipping them with modern knowledge is a national priority in educational policy.